A case report on fatal intoxication by tapentadol: Study of distribution and metabolism. (July 2021) - Carelli, Claudia; Freni, Francesca; Moretti, Matteo; Vignali, Claudia; Ballardini, Marco; Morini, Luca
Highlights: Tapentadol past intake consumption is detectable through hair analysis. Phase II metabolites represent the most abundant ones for tapentadol. A blood level of 520.0 ng/mL can cause severe respiratory depression. Abstract: We report a case in which a tapentadol acute intoxication was suspected as the cause of death of a 39-year-old man: approximately two days after death, cardiac and femoral blood, as well as urine, bile, gastric content and chest hair, were collected during the autopsy. Tapentadol was detected before and after hydrolysis in femoral (530 ng/mL unconjugated and 1570 ng/mL conjugated) and cardiac (680 ng/mL unconjugated and 3440 ng/mL conjugated) blood, and additionally in bile (3200 ng/mL), urine (9300 ng/mL), chest hair (2850 pg/mg) and gastric content. LC-QTOF screening analysis confirmed the presence of five different tapentadol metabolites (tapentadol-O-glucuronide, tapentadol-O-sulfate, N-desmethyltapentadol, N-desmethyltapentadol-glucuronide and N-desmethyltapentadol-O-sulfate), in urine, bile, cardiac and femoral blood. Positivity of body hairs allowed us to conclude that the man had used tapentadol in the last weeks/months. Autopsy and toxicological results (also positive for clotiapine, diazepam and chlordesmethyldiazepam) suggested that tapentadol could have caused, even at low concentrations, a severe respiratory depression, which contributed to the death of the subject. This is one of the few cases in literature where tapentadol was detected in blood, together with its metabolites, and the only one in which the parent drug was identified in hairs.